JURNAL AYURVEDA MEDISTRA - Simamora, Rotua Suriany (STIKes Medistra Indonesia, 2019)
ABSTRACT INFLUENCE OF HEALTH EDUCATION ON INITIAL SCREENING OF HIV/AIDS ON FEMALE SEX WORKERS IN SUNGAI BUNTU VILLAGE OF KARAWANG 2018 HIV/AIDS is one of health problems that cause a very wide impact and has not found a healing vaccine so far. Transmission of HIV infection mainly occurs through sexual intercourse, therefore HIV/AIDS prevention is focused on safe and responsible sexual behavior. Prevention for HIV-infected risk groups (female sex workers) is aimed at turning risky behavior into safe behavior. Intervention programs to minimize HIV/AIDS prevalence are health education, VCT screening (voluntary counseling and tasting). The low knowledge and awareness of the community, especially female sex workers on health and disease make it difficult to detect the disease, it is difficult to be examined and treated the disease. of this research was to know the influence of health education on initial screening of HIV/AIDS on female sex workers in Sungaibuntu village of Karawang 2018. Research design used was quasi experiment by One Group Pretest Posttest. Population was all female sex workers in Sungaibuntu village of Karawang 2018 by sample was as many as 12 people. Data collection technique was by total sampling. Research instruments used questionnaire. Analysis by bivariate using Dependent T-Test statistical test. obtained that few respondents who wanted to perform HIV/AIDS screening before health education (25%) and all respondents wanted to perform HIV/AIDS screening after health education (100%). There is mean difference before (17.25) and after (31.00) health education is conducted. There is significant influence of health education on initial screening of HIV/AIDS on female sex workers in Sungaibuntu village of Karawang 2018 by p-value = 0.000.